Pemanfaatan Limbah Cair Biogas Sebagai Pupuk Organik Untuk Kangkung Darat (Ipomoea reptans Poir.) Di Daerah Transmigrasi Masni Kabupaten Manokwari - Marselius O. Y. A. W. Mra-Mra; Djoko Sudjatno; Kati Syamsudin (Agrotek, 2012)
The research aimed to see the usage of liquid biogass waste (LBW) as a fertilizer on the growth of pokcoy (Ipomoea reptans Poir.). In transmigration area, Masni Manokwari. It used experiment method with rondom plot design. There were six treatments, without LBW (A0), 50 cc of LBW (A1), 100 cc of LBW (A2), 150 cc of LBW (A3), 200 cc of LBW (A4), and 250 cc of LBW (A5). The result showed that LBW had significant effect on plant height (6 week after plantation), fresh weight per plant and per plot, dry weight per plant and water content per plant. These indicated that application on of LBW increased yield of pokcoy. The dose 250 cc of LBW was significantly enhanced the growth and yield of pokcoy.